2020
DOI: 10.1002/jbm.a.37126
|View full text |Cite
|
Sign up to set email alerts
|

Tissue response to biphasic calcium phosphate covalently modified with either heparin or hyaluronic acid in a mouse subcutaneous implantation model

Abstract: Biphasic calcium phosphate (BCP) materials are widely employed as bone substitute materials due to their resorption/degradation properties. Inflammation after implantation of such materials represents a prerequisite for bone tissue repair and regeneration but can be also problematic if it is not only transient and if it is followed by fibrosis and scarring. Here, we modified BCP covalently with hyaluronan (HA) and heparin (Hep), glycosaminoglycans that possess anti‐inflammatory properties. Beside the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…In this scenario, all manner of biomaterial, in combination with various cell types and small molecules, can be assessed for their ability to induce bone formation in the absence of surrounding bone-forming cells or a bony environment. (198)(199)(200) This can be very useful to remove any confounding effects of endogenous factors or cells on the experimental outcome. The model has further advantages of being minimally invasive and simple to perform.…”
Section: Large Animal Modelsmentioning
confidence: 99%
“…In this scenario, all manner of biomaterial, in combination with various cell types and small molecules, can be assessed for their ability to induce bone formation in the absence of surrounding bone-forming cells or a bony environment. (198)(199)(200) This can be very useful to remove any confounding effects of endogenous factors or cells on the experimental outcome. The model has further advantages of being minimally invasive and simple to perform.…”
Section: Large Animal Modelsmentioning
confidence: 99%
“…The skin on the back was shaved, washed with povidone iodine and incision was made. One film, 13 mm in diameter, was implanted per animal, subcutaneously, just below the interscapular region as previously published [38][39][40]. Each experimental group consisted of 15 animals carrying the same sample type.…”
Section: In Vivo Biocompatibility Studiesmentioning
confidence: 99%
“…Bone grafts containing biphasic calcium phosphate are extensively used due to their favorable properties of resorption and degradation [ 14 ]. However, some studies have shown that synthetic materials are less effective in cases where extensive and complex regeneration is required [ 15 ].…”
Section: Introductionmentioning
confidence: 99%